Impact of Short- and Medium-Chain Fatty Acids on Mitochondrial Function in Severe Inflammation. (July 2014) - Hecker, Matthias; Sommer, Natascha; Voigtmann, Hans; Pak, Oleg; Mohr, Andrea; Wolf, Martin; Vadász, István; Herold, Susanne; Weissmann, Norbert; Morty, Rory E.; Seeger, Werner; Mayer, Konstantin
Background : Sepsis is a severe inflammatory disorder with a high mortality in intensive care units mostly due to multiorgan failure. Mitochondrial dysfunction is regarded as a key factor involved in the pathogenesis of septic disorders, leading to a decline in energy supply. The aim of the present study was to evaluate whether application of short-chain fatty acids (SCFAs) and medium-chain fatty acids (MCFAs) could improve mitochondrial function and thus might serve as a potential energy source under inflammatory conditions. Materials and Methods : As an experimental approach, starved human endothelial cells and monocytes were incubated with hexanoic acid, heptanoic acid, octanoic acid, or glucose and subsequently subjected to high-resolution respirometry to assess mitochondrial function under baseline conditions. In a second set of experiments, cells were pretreated with tumor necrosis factor–α to mimic inflammation and sepsis. Results : We demonstrated that addition of SCFAs and MCFAs increases mitochondrial respiratory capacity at baseline and inflammatory conditions in both cell types. None of the fatty acids induced changes in mitochondrial DNA content or the generation of proinflammatory cytokines, indicating a beneficial safety profile. Conclusion : We deduce that SCFAs and MCFAs are suitable and safe sources of energy under inflammatory conditions with the capability to partly restore mitochondrial respiration.